Cholate-forming function of the liver in patients with chronic alcoholism - Anokhina, G A; Furmanets, T A; Fedishin, P S; Grigorash, G A; Nemilostivyĭ, A I (Vrachebnoe delo, 1989)
The level of bile acids was studied in the bile and feces in 119 patients with chronic alcoholism using thin-layer chromatography. The cholate-forming function of the liver was found to increase in patients with short alcohol anamnesis in chronic alcoholism. With advance of the alcohol anamnesis the number of patients with reduced cholate-forming function of the liver increased.